Primary Rotator Cuff Bridging Reconstruction Shows Better Clinical and Radiographic Results Than Revision Bridging Reconstruction - Jillian Karpyshyn, M.D., F.R.C.S.C; Sara Sparavalo, M.A.Sc; Jie Ma, M.E.S; John-Paul King, M.D; Ivan Wong, M.D., F.R.C.S.C., M.A.C.M., F.A.A.N.A (Elsevier, 2024)
Purpose: To evaluate the outcome of revision rotator cuff bridging reconstruction (BR) as compared to primary BR in a large cohort of patients. Methods: A retrospective chart review was conducted for patients who underwent BR using dermal allograft for large/massive rotator cuff tears between 2010 and 2018. Patients who completed Western Ontario Rotator Cuff Index (WORC) and Disability of the Arm, Shoulder, and Hand (DASH) scores both pre- and postoperatively were included. Pre- and postoperative magnetic resonance imaging scans were compared to assess for differences in fatty infiltration, muscle atrophy, and graft status. Results: Eighty patients met the inclusion criteria, including 43 patients who underwent BR as a primary surgery and 37 patients who underwent revision BR. The mean follow-up duration was 5.7 ± 1.9 years in the primary group and 5.8 ± 2.0 years in the revision group. Both WORC and DASH scores significantly improved from pre- to postoperatively for both the primary and revision groups (P < .05). The primary group had significantly better postoperative WORC and DASH scores at 6 months, 1 year, and final follow-up (P < .05). Failure rate of the graft was higher in the revision group compared to primary group (14.3% vs 6.1%, respectively; P = .337), and the amount of fatty infiltration of supraspinatus and infraspinatus muscles significantly improved in patients who received primary BR compared to revision BR (P < .05). Conclusions: BR using dermal allograft for large/massive irreparable rotator cuff tears showed improvement of functional outcomes, with primary cases resulting in better improvement in patient-reported outcomes compared to revision cases. Primary BR was also associated with better postoperative fatty infiltration of supraspinatus and infraspinatus muscles. Level of Evidence: Level III, retrospective cohort study.